MAIZE STORAGE IN TERMITE MOUND CLAY, CONCRETE, AND STEEL SILOS IN THE HUMID TROPICS: COMPARISON AND EFFECT ON BACTERIAL AND FUNGAL COUNTS (2015)
Considering the inadequacy of grain storage structures in Nigeria, which has been partly attributed to high cost and unavailability of construction materials, this study investigated the suitability of using readily available termite mound clay (TMC) for grain silo construction in comparison to conventional reinforced conczu (RC) and galvanized steel (GS) silos for maize storage in the humid tropics. The extent to which temperature and relative humidity affected the quality of stored grain during 8-month unaerated storage, covering both dry and rainy seasons, was evaluated using bacterial and fungal counts as performance parameters. The initial bacterial count of3500 colony forming units (CFU) per gram (CFU g-1) increased to 120000, 11000, and 8800 CFU g-1 for TMC, RC, and GS silos, respectively. There was no fungal activity at the beginning of storage, but fungal activity increased to 1500, 5500, and 350 CFU g-1 in TMC, RC, and GS silos, respectively. Fungal activity was noticed in the TMC silo in the fourth month of storage, which coincided with the start of the rainy season. Fungal counts exceeded the acceptable threshold of 1000 CFU g-1 in the TMC and RC silos. Relative humidity was of greater significance than temperature in affecting all. maize quality parameters considered. TMC was found suitable for constructing silos for short-term grain storage under unaerated conditions. Modification of the current TMC silo design to address permeability issues is expected to improve its performance for longer-term maize storage.